Single‐run HPLC/ESI‐LITMS profiling of ginsenosides in plant extracts and ginseng based products. (30th October 2014) - Stavrianidi, Andrey; Rodin, Igor; Braun, Arkady; Stekolshchikova, Elena; Shpigun, Oleg
Abstract A rapid single‐run analytical approach suitable to achieve a comprehensive characterization of ginsenosides – the main bioactive compounds present in plant materials from Panax species and ginseng‐based products – was developed. The method is based on high‐performance liquid chromatography coupled with electrospray positive ionization linear ion trap mass spectrometry (HPLC/ESI‐LITMS). The main ions in the ESI‐LITMS spectra were attributed to molecular adducts with sodium and potassium and fragments corresponding to cleavage of the glycosidic bonds. The simplicity of the approach allows laborious sample preparation and sophisticated spectral information‐dependent acquisition to be avoided, and provides an opportunity for rapid screening. The method may replace existing HPLC‐DAD profiling approaches. The results of this study indicate that HPLC/ESI‐LITMS is applicable for quality control purposes on processed products and allows the rapid and direct identification of ginsenosides in crude plant extracts. Copyright © 2014 John Wiley & Sons, Ltd.